Community’s Response Toward The Study Program Of Al-Qur’an Science And Tafsir - Ali Sati; Anhar Anhar (FITRAH: Jurnal Kajian Ilmu-ilmu Keislaman, 2020)
The purpose of this study is to find out how the community's response is toward the study program of Al-Qur'an and Tafsir at IAIN Padangsidimpuan. This research is a qualitative research which in collecting data it uses a phenomenological approach. Data collected is based on inner perspective of human behavior. The main data sources of this study were from Muslim community leaders and were selected by purposive sampling domiciled in Padangsidimpuan. The results found that the community emphasized that the vision, mission and objectives of the development of the Study Program of Al-Qur'an and Tafsir were truly directed towards strengthening scientific and methodological competence in understanding and interpreting the Qur'an. According to the community, the urgent curriculum content was, first, the linguistics of the Qur'an. The second is the sciences concerned the intricacies and various aspects of the Qur'an, which is commonly called ‘ulum al-Qur`an. The third is about the sciences related to the interpretation of manhaj (an approach and methodology of interpretation) that is classical, modern and contemporary. The fourth is the sciences related to the intricacies and various aspects of the hadits which are commonly called ‘ulum al-hadits. The fifth is the sciences related to the philosophy of science and research methodology. The sixth is the sciences related to social science and nature. These aspects are useful for understanding the social and scientific aspects of the verses of the Qur'an.